ASPEK STRATEGIS PENGELOLAAN DANAU TONDANO SECARA TERPADU - Veronica Kumurur (PPLH-SDA, Lembaga Penelitian Unsrat Manado, 2012)
In natural resources management, a strategy is significant important, especially in lake management. The management strategy should be analyzed prior in regard to conservation aspect before it is implemented. Nowadays, Tondano Lake needs a great concern for its sustainable water resources and it needs actions in a management context. Aspects should be focused in the strategic management are water uses, biodiversity, run-off pollution, and water surface level. All aspects should be analyzed in order to establish a strategic management plan for Tondano Lake.